Effects of tadalafil to prevent injury on corpus cavernosum after vascular or nervous peri-prostatic bundle injury. Experimental model in rats - De Toledo, Antônio Carlos [UNESP]; Kawano, Paulo Roberto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Guerra, Rodrigo [UNESP]; Filho, Fernando Ferreira Gomes [UNESP]; Pajolli, Pedro Ivo Rochetti [UNESP]; Amaro, João Luiz [UNESP]; Cardoso, Luiz Eduardo Macedo; Sampaio, Francisco José (FapUNIFESP (SciELO), 2019)
Purpose: To evaluate the effects of tadalafil (TD) in preventing histological alterations of the corpus cavernosum caused by isolated lesions of cavernous nerve (ILCN) and artery (ILCA) in rats. Methods: Fifty male Wistar rats were randomly assigned in five groups: G1: Control; G2: Bilateral ILCN; G3: Bilateral ILCA; G4: ILCN+TD; G5: ILCA+TD. The cavernous bodies were submitted to histomorphometry, immunohistochemistry and biochemical analysis. Results: Nerve density was significantly higher in G2 and G4 compared to control (22.62±2.84 and 19.53±3.47 vs. 15.72±1.82; respectively, p<0.05). Smooth muscle density was significantly lower in G2 and G3 in comparison to G1 (12.87±1.90 and 18.93±1.51 vs. 21.78±1.81, respectively; p<0.05). A significant decrease in the sinusoidal lumen area was observed in G2 compared to controls (5.01±1.62 vs. 9.88±3.66, respectively; p<0.05) and the blood vessel density was increased in G2 and G3 (29.32±4.13 e 20.80±2.47 vs. 10.13±2.71, p<0.05). Collagen density was higher in G3 compared to G1 (93.76±15.81 vs. 64.59±19.25; p<0.05). Conclusions: Histomorphometric alterations caused by ILCN were more intense than those produced by vascular injury, but the collagen analyses showed more fibrosis in animals with ILCA. TD was effective in preventing the majority of the alterations induced by the periprostatic bundle injury.
Keywords: Collagen; Elastin; Erectile Dysfunction; Rats; Tadalafil